2017
DOI: 10.1016/j.aprim.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Alfabetización en salud en pacientes con insuficiencia cardiaca atendidos en atención primaria

Abstract: In patients with stable heart failure, it is important to consider all factors that help patients to understand the healthcare information. Health literacy explains patient self-care attitude in heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 30 publications
3
11
0
7
Order By: Relevance
“…These results are very similar to a previous study in Taiwan, which was also conducted in an urban hospital involving inpatients diagnosed with NYHA II and III heart failure, and in which 60.2% of the respondents showed inadequate health literacy [12]. A previous study [25] conducted in Spain showed a higher level of limited health literacy (79.6%) in patients with heart failure in the primary health care sector.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These results are very similar to a previous study in Taiwan, which was also conducted in an urban hospital involving inpatients diagnosed with NYHA II and III heart failure, and in which 60.2% of the respondents showed inadequate health literacy [12]. A previous study [25] conducted in Spain showed a higher level of limited health literacy (79.6%) in patients with heart failure in the primary health care sector.…”
Section: Discussionsupporting
confidence: 89%
“…The questionnaire has already been used to test the literacy of specific groups of patients, such as adolescents [3], diabetics [3,24], and patients with heart failure [25]. We used the full version of the questionnaire with a cultural adaptation (linguistic validation) to the Serbian language.…”
Section: Methodsmentioning
confidence: 99%
“…Concerning age, recent studies in heart failure patients inversely relate age to HL scores [12,[32][33][34]. In our study, equally, older patients were less able to navigate the health system to address their needs on their own, did not understand most health information, had great difficulty filling out medical forms and were confused before conflicting information, depending on others to enable the access to health resources.…”
Section: Discussionmentioning
confidence: 53%
“…Por otra parte, el autocuidado de la dieta mostró correlación significativa con la AS en todas sus dimensiones y capacidades con excepción de la dimensión procesar/juzgar. Esto concuerda con lo reportado por Santesmases, et al, quienes encontraron que las pobres conductas de autocuidado se relacionan con el bajo nivel de comprensión de la información en salud (27) . Si bien en la presente investigación, dado su diseño transversal, no es posible establecer causalidad, si apunta a una relación que pudiera ser sumamente útil en términos de prevención por lo que merece su estudio en investigaciones longitudinales.…”
Section: Discussionunclassified
“…Es por ello que se debe plantear nuevas estrategias educativas que faciliten el proceso de comprensión de dicha información y tener presente que a medida que la edad avanza, el acompañamiento tanto de los profesionales de la salud como de las redes de apoyo social requiere ser más cercano para facilitar que sigan las recomendaciones de los profesionales de la salud. En algunos estudios se ha señalado que el crear intervenciones utilizando formatos como dibujos e imágenes podrían ayudar a comprender mejor los temas de promoción de la salud y con ello mejorar la AS (23,27) .…”
Section: Discussionunclassified